Generation of sub-two-cycle pulses tunable around 1.8 μm with passively stabilized carrier-envelope phase at 100 kHz repetition rate - Homann, C.; Bradler, M.; Foerster, M.; Hommelhoff, Peter; Riedle, Eberhard (EPJ Web of Conferences, 2013)
We present an efficient concept for generating carrier-envelope phase stable pulses tunable between 1.6 and 2.0 μm with durations down to 8.2 fs based on nonlinear frequency conversion. As a first application we measure the high nonlinearity of multiphoton photoemission from a nanoscale metal tip. © Owned by the authors, published by EDP Sciences, 2013.
CRIS-Team Scopus Importer:2023-03-07